2021
DOI: 10.3233/jad-201137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Memantine Treatment and Combination with Vitamin D Supplementation on Body Composition in the APP/PS1 Mouse Model of Alzheimer’s Disease Following Chronic Vitamin D Deficiency

Abstract: Background: Vitamin D deficiency and altered body composition are common in Alzheimer’s disease (AD). Memantine with vitamin D supplementation can protect cortical axons against amyloid-β exposure and glutamate toxicity. Objective: To study the effects of vitamin D deprivation and subsequent treatment with memantine and vitamin D enrichment on whole-body composition using a mouse model of AD. Methods: Male APPswe/PS1dE9 mice were divided into four groups at 2.5 months of age: the control group (n = 14) was fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…Interestingly, the current study showed that vitamin D deficiency led to an increase in hind stride width, a marker of balance and postural control [3], by month 15 of the study. We have previously shown that vitamin D deficiency does not cause any changes in body composition in APPswe/PS1dE9 mice [24], however it is possible that vitamin D deficiency affected gait through neurological processes. Another study in APPswe/PS1dE9 mice found progressive development of morphological abnormalities in the cerebellar cortex resulting in decreased performance in wirehanging and rotarod tests [22].…”
Section: Effect Of Vitamin D Deprivationmentioning
confidence: 93%
“…Interestingly, the current study showed that vitamin D deficiency led to an increase in hind stride width, a marker of balance and postural control [3], by month 15 of the study. We have previously shown that vitamin D deficiency does not cause any changes in body composition in APPswe/PS1dE9 mice [24], however it is possible that vitamin D deficiency affected gait through neurological processes. Another study in APPswe/PS1dE9 mice found progressive development of morphological abnormalities in the cerebellar cortex resulting in decreased performance in wirehanging and rotarod tests [22].…”
Section: Effect Of Vitamin D Deprivationmentioning
confidence: 93%
“…A software utility was written to compute the mass of the adipose tissue by multiplying the volume by a predetermined density (0.90 g/cm 3 ). Similarly, skeletal tissue volume was computer using image values of above 190 HU and the mass computer by multiplying the volume with a density of 1.92 g/cm 3 22 …”
Section: Methodsmentioning
confidence: 99%
“…These findings, however, do not preclude the potential clinical benefit of vitamin D supplementation on lower AD risk in younger or middle-aged people before the disease has taken its toll and before AD damage has become irreversible. Supporting this notion, several animal studies have reported that starting vitamin D supplementation at very early stage of disease in AD mice, when amyloid plaques are far from being developed, may benefit AD (Landel, Millet, et al, 2016b;Morello et al, 2018;Wong et al, 2021;Yu et al, 2011). Therefore, timing of supplementation is perhaps an important factor to consider.…”
Section: Iscuss E Smentioning
confidence: 99%